Comparative study on the effect of ultrasonic instruments on the root surface in vivo - Santos, Fabio Andre; Pochapski, Marcia Thais; Leal, Paola Cristina [UNESP]; Gimenes-Sakima, Patricia Panizzi [UNESP]; Marcantonio, Elcio [UNESP] (Springer Heidelberg, 2008)
The present study was designed to investigate the effectiveness of different ultrasonic instruments on the root surface. Fourteen patients with 35 single root teeth designated for extraction were recruited to the present study. Teeth were assigned to four experimental groups: group 1, piezoelectric ultrasonic device; group 2, magnetostrictive ultrasonic device; group 3, hand instrumentation; and group 4, untreated teeth (control). After instrumentation, the teeth were extracted and the presence of residual deposits (roughness and root surfaces characteristics) were analyzed. The results showed that residual deposits were similar in all tested groups: piezoelectric, 8.7%; magnetostrictive, 9.7%; hand instrumentation, 11.1% and control, 76.4%. There were statistically significant differences between control and all the experimental groups (p < 0.0001). With respect to roughness parameters evaluation, R(a) and R(z) of the roots treated with the different instruments showed a similar pattern (p > 0.05), but for R(t) and R(y), a significant difference was observed (p < 0.05) among hand instrumentation and ultrasonic devices. SEM analysis revealed a similar root surface pattern for the ultrasonic devices, but curettes showed many instrumental scratches, deep gouges, and a relatively large amount of dentin was removed. Within the limits of the study, although the instruments produced similar results, root surfaces instrumentated with curettes were rougher and had more root surface tissue removed than with the ultrasonic device.
Keywords: dental scaling; root planning; dental instruments; dental calculus; dental plaque